MO026CLINICAL AND MUTATIONAL SPECTRUM OF CHILDREN WITH AUTOSOMAL RECESSIVE AND AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE. (29th May 2021) - Tutal, Ozum; Gulhan, Bora; Atayar, Emine; Yuksel, Selcuk; Ozcakar, Z Birsin; Soylemezoglu, Oguz; Saygili, Seha; Inozu, Mihriban; Baskin, Esra; Duzova, Ali; Hayran, Mutlu; Topaloglu, Rezan; et al.
Abstract: Background and Aims: Cystic kidney diseases are a heterogeneous group of chronic renal disease. Autosomal recessive polycystic kidney disease (ARPKD) is generally diagnosed in utero or at birth due to mutations in PKHD1 gene. Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease commonly associated with mutations in PKD1 or PKD2. In this study, we aimed to investigate clinical and genetic features of ARPKD and ADPKD in a group of Turkish patients. Method: A total of 69 children with genetically confirmed ARPKD (10 females, 11 males) or ADPKD (28 females, 20 males) from seven pediatric nephrology centers were included in this study. Demographic features, family history, clinical and laboratory findings at presentation and during 12 months intervals were collected. Results: For ARPKD patients, the median age at diagnosis was 10.5 (IQR; 0.75-58.5) months. Consanguinity between parents was present in 11 patients (52.4%). At the time of diagnosis, 14 (66.7%) patients had eGFR<90 ml/min/1.73 m2. Mean duration of follow-up was 4.1±3, 7 years. At the last visit, median eGFR was 74 (IQR; 43-126) ml/min/1.73m2. A total of 6 patients (28, 6%) underwent a renal replacement therapy (RRT), 3 of them died in infancy and 2 of them had renal transplantation during follow up. All patients had bi-allelic PKHD1 mutation. For ADPKD patients, the mean age at diagnosis was 5.5±4.6 years. At the time of diagnosis 11 (22.9%) patients had eGFR<90 ml/min/1.73m2. Mean duration of follow-up was 2, 7±2.3 years. At the last visit, median eGFR was 114 (IQR; 98-135) ml/min/1.73m2. Only one patient underwent a renal transplantation. A total of 42 patients (87.5%) had a heterozygous PKD1 mutation while 6 (12.5%) had a heterozygous PKD2 mutation. The rate of growth retardation, hypertension at diagnosis and progression to chronic kidney disease (CKD) were higher in patients with PKHD1 mutation than the patients with PKD1 or PKD2 mutation (p < 0.001, p < 0.001 and p = 0.001, respectively). In kidney survival analysis, mutation type, growth retardation at presentation, increased renal echogenity in ultrasonography were found as independent risk factors for progression to CKD. Conclusion: Cystic kidney diseases are one of the most clinically and genetically heterogenous diseases. Differentiating them and establishing the predictors for CKD development is important to provide appropriate management including choosing appropriate donor in renal transplantation.